Artificial intelligence and intellectual property : who owns property created by an algorithm or a robot? - Schiemer, Jordan; Tawse, Nicholas; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
The University of Surrey has filed multiple patents in the United Kingdom on behalf of an Artificial Intelligence (AI) Robot, Device for the Autonomous Bootstrapping of Unified Sentience (DABUS). The two ideas were artificially created by DABUS without any human intervention, but for centuries, intellectual property ownership has been created on behalf of humans. With improving computing power and abilities of Artificial Intelligence, the need to copyright for non-human beings is being called to question. This case study analyses the question: should the University of Surrey, or any other entity, be allowed to apply for intellectual property protection on behalf of an AI robot or algorithm?
Originally Published In Schiemer, J., Tawse, N., & O'Rourke, J. S. (2019). Artificial Intelligence and Intellectual Property: Who Owns Property Created by an Algorithm or a Robot?. 19-15. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Intellectual property -- England -- Surrey -- Case studies; Artificial intelligence -- Law and legislation -- England -- Surrey -- Case studies